Research Progress of Mobile Medical Technology in Home Cardiac Rehabilitation Nursing - Huang, Ruiyan (International Journal of Public Health and Medical Research, 2026)
In recent years, due to the increasing incidence of cardiovascular diseases and the lack of medical resources, the traditional hospital based cardiac rehabilitation is difficult to meet the needs of patients. Mobile medicine has the characteristics of being anytime, anywhere, convenient and fast, which can better expand cardiac rehabilitation to the home. This article provides a review of the relevant research on the application of mobile medicine in home cardiac rehabilitation nursing: summarizing its core carrier role, main application methods, and further improvement directions. In summary, mobile healthcare can provide assistance for remote follow-up, personalized management, health education, and psychological counseling, playing a positive role in improving rehabilitation rates, compliance, and prognosis. The next step should start with technology integration, precision services, cross disciplinary cooperation, and the establishment of relevant systems, aiming to promote the standardization and sustainability of home-based cardiac rehabilitation.